2015
DOI: 10.1039/c5ay00547g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of uncertainty in the energy dispersive X-ray fluorescence determination of platinum in alumina

Abstract: Uncertainty, the most important characteristic of an analytical result, has been evaluated using a bottom-up approach during EDXRF determination of Pt in alumina. The calibration function of the EDXRF spectrometer was derived through bivariate least squares fitting, in combination with weighted regression of the residuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Detection limit of EDXRF spectrometry for Hg in the present studies was found to be 22 ng, as calculated from the blank, i.e. background counts in the region of interest . The detection limit of Hg is 2 ng ml −1 for the CVAAS technique .…”
Section: Resultsmentioning
confidence: 42%
“…Detection limit of EDXRF spectrometry for Hg in the present studies was found to be 22 ng, as calculated from the blank, i.e. background counts in the region of interest . The detection limit of Hg is 2 ng ml −1 for the CVAAS technique .…”
Section: Resultsmentioning
confidence: 42%
“…These characteristics can be summarized in terms of the effective sample thickness, calculated based on the mass attenuation coefficients of each component element and the mass thickness of the samples. Depending on the effective mass attenuation coefficients, samples are divided into three categories, namely, thin, thick, and intermediate thickness, which, in turn, decides the quantification methodology in EDXRF measurements …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the effective mass attenuation coefficients, samples are divided into three categories, namely, thin, thick, and intermediate thickness, which, in turn, decides the quantification methodology in EDXRF measurements. [19,20] The calibration standards for the present studies were evaluated for their thickness characteristics, considering the mass attenuation coefficients and weight fractions of each element as per the proportion of the constituents, namely, the Fe 2 O 3 standard and cellulose. The effective thicknesses were calculated for a combination of 12-keV source X-rays and 6.4-keV characteristic X-rays.…”
Section: Assessment Of Calibration Standards For Quantification Of mentioning
confidence: 99%
“…The paper argues that the bottom-up method for MU estimation is feeble as long as the sensitivity coefficients of the uncertainty budget factor are not well known and documented, which is the habitual case of the ED and WD XRFS bottom-up published methods [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature one can found a lot of modelling approaches for ED-XRFS and WD-XRFS [22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%